Kontestasi Identitas dan Kesalehan Anak Usia Dini Islam dalam Animasi Nussa - Mustakim, Bagus (Al-Athfal: Jurnal Pendidikan Anak, 2019)
Discussion of the piety of early childhood, currently in the shadow of an ideological debate of various political, social and religious identities. This kind of ideological debate is increasing along with the expansion of global social media networks in the digital age. In this ideological debate, a phenomenal animated film called "Nussa" emerged. This article focuses on the piety of early Islamic childhood represented by Nussa animation on the Youtube channel. The problem formulated in this article is why Nussa animation is offered as the piety of Islamic early childhood; How is the construction of early childhood piety offered in this animation; and how is this identity promoted? This article was developed with a media and cultural study approach. This research uses qualitative methods with the phenomenological approach and interpretive discourse analysis methods. The author finds that the animation of Nussa actively produces piety as the identity of early Islamic childhood in ideological contestation with globalism and secular modernism. This piety is offered as an authentic Islamic identity for Islamic early childhood.